The macroeconomic effects of asset purchases revisited - Henning Hesse; Boris Hofmann; James Weber (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
This paper revisits the macroeconomic effects of the large-scale asset purchase programmes launched by the Federal Reserve and the Bank of England from 2008. Using a Bayesian VAR, we investigate the macroeconomic impact of shocks to asset purchase announcements and assess changes in their effectiveness based on subsample analysis. The results suggest that the early asset purchase programmes had significant positive macroeconomic effects, while those of the subsequent ones were weaker and in part not significantly different from zero. The reduced effectiveness seems to reflect in part better anticipation of asset purchase programmes over time, since we find significant positive macroeconomic effects when we consider shocks to survey expectations of the Federal Reserve's last asset purchase programme. Finally, in all estimations we find a significant and persistent positive impact of asset purchase shocks on stock prices.
urn:nbn:de:hebis:30:3-457710
Keywords: E50; E51; E52; 330; unconventional monetary policy; asset purchases; monetary transmission